A Qualitative Study on Parental and Community Stakeholder Views of the Link between Full-Day Kindergarten and Health in Southern Nevada - Courtney Coughenour; Jennifer Pharr; Maxim Gakh; Sheila Clark; Prescott Cheong (MDPI AG, 2019)
Studies show that children who attend full-day kindergarten (FDK) experience both academic and developmental benefits compared to children who attend half-day programs. Sectors outside of health, such as education, can have important intended and unintended impacts on health. The purpose of this qualitative study was to understand perceptions of parental and other stakeholders in Southern Nevada (USA) about the education⁻health link, and to understand priorities regarding how FDK access could affect health. Two 90-minute focus groups were conducted with 14 adult stakeholder participants representing parents, current and former teachers, and community members. Transcripts were analyzed using conventional content analysis. Eight major themes and several subthemes emerged; findings related to each are discussed. ‘Access’ was mentioned most frequently (n = 43), followed by ‘Time’ (n = 25), and ‘Lifetime educational attainment’ (n = 17). Participants were overall in favor of expanding access to FDK and felt that FDK could improve social skills, increase the amount of physical activity, and provide additional time for educators to detect additional learning disabilities when compared to half-day programs. Although the purpose was to understand priorities related to the education⁻health link, participants spent little time discussing this, suggesting this association is not inherently considered. Health and education stakeholders should collaborate to increase awareness, as this link may serve as an upstream approach to downstream effects on population health outcomes.